2022
DOI: 10.1037/ebs0000243
|View full text |Cite
|
Sign up to set email alerts
|

The effect of eyelash length on attractiveness: A previously uninvestigated indicator of beauty.

Abstract: Human eyelashes are one of the facial features that contributes to facial attractiveness. While enhancing the appearance of eyelashes has been practiced since antiquity, research investigations that consider the effect of their length on perceived attractiveness are scarce. Length of eyelashes can be an indicator of health, and it has recently been proposed that there is an optimum length for eye protection. In the current article, we investigated if the attractiveness of eyelash length dovetails with these ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 19 publications
4
13
0
1
Order By: Relevance
“…These studies have shown that facial features might be regarded differently and preferred by one's own-ethnicity compared to other ethnicities 10 , 17 . Therefore, the findings by Pazhoohi and Kingstone 1 might not generalize across different ethnicities. In other words, it is crucial to examine whether the previous finding with an inverted-U pattern 1 will be generalized and observed across diverse ethnicities.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…These studies have shown that facial features might be regarded differently and preferred by one's own-ethnicity compared to other ethnicities 10 , 17 . Therefore, the findings by Pazhoohi and Kingstone 1 might not generalize across different ethnicities. In other words, it is crucial to examine whether the previous finding with an inverted-U pattern 1 will be generalized and observed across diverse ethnicities.…”
Section: Introductionmentioning
confidence: 91%
“…Pazhoohi and Kingstone 1 introduced the possibility that the perception of eyelash length attractiveness might dovetail with the proposed phylogenetically adaptive functionality of eyelash length 2 . Specifically, arguing from an adaptive evolutionary perspective that attractiveness is an honest signal of health and genetic quality 3 , 4 , Pazhoohi and Kingstone 1 proposed that eyelash length should be perceived as most attractive at the length where: (a) it has the highest functionality in minimizing evaporation and contamination at the ocular surface 2 , and (b) it is associated with the highest health condition of the eyelashes 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eyeliner can also make the eyes appear larger ( Matsushita et al, 2015 ) and create the appearance of a whiter sclera, which can enhance perceptions of attractiveness ( Provine et al, 2013 ). Similarly, long eyelashes, which men find attractive ( Pazhoohi & Kingston, 2020 ), can be modified with mascara or eyelash conditioners and serums. The underlying assumption for these effects is that women exaggerate facial features that have been shaped by sexual selection to advertise aspects of their physical condition ( Batres et al, 2018 ; Davis & Arnocky, 2020 ; Jones & Kramer, 2015 ).…”
Section: Self-presentation Modifications: Appearance Enhancing and Wo...mentioning
confidence: 99%